Convergent close-coupling calculations of helium single ionization by antiproton impact - Abdurakhmanov, Ilkhom; Kadyrov, Alisher; Fursa, Dmitry; Bray, Igor; Stelbovics, Andris (American Physical Society, 2011)
We apply the fully quantum-mechanical convergent close-coupling method to the calculation of antiproton scattering on the ground state of helium. The helium target is treated as a three-body Coulomb system using frozen-core and multiconfiguration approximations. The electron-electron correlation of the target is fully treated in both cases. Though both calculations yield generally good agreement with experiment for the total ionization cross sections, the multiconfiguration results are substantially higher at the lower energies than the frozen-core ones. Calculated longitudinal ejected electron and recoil-ion momentum distributions for the single ionization of helium are in good agreement with the experiment.